OP33 Oral ritlecitinib and brepocitinib in patients with Moderate to Severe Active Ulcerative Colitis: Data from the VIBRATO umbrella study. (27th May 2021) - Sandborn, W; Danese, S; Leszczyszyn, J; Romatowski, J; Altintas, E; Peeva, E; Vincent, M; Reddy, P; Banfield, C; Banerjee, A; Gale, J; Hung, K
Abstract: Background: The efficacy and safety of oral ritlecitinib (JAK3/TEC inhibitor) and brepocitinib (TYK2/JAK1 inhibitor) were assessed in a 32-week Phase 2 b induction-maintenance umbrella study (VIBRATO) in participants with moderate to severe active ulcerative colitis who had inadequate or loss of response, or intolerance to corticosteroids, immunosuppressants, or biologic therapies. We report efficacy and safety results from the 8-week induction period of the VIBRATO study. Methods: Adult participants with Total Mayo Score ≥6 and centrally-read Mayo endoscopic subscore ≥1 were randomised to receive oral ritlecitinib 20, 70, or 200 mg; brepocitinib 10, 30, or 60 mg; or placebo once-daily (QD) for 8 weeks. Participants then continued in their respective treatment cohorts to receive ritlecitinib 50 mg or brepocitinib 30 mg QD for 24 weeks. The proportions of patients who achieved remission (Total Mayo Score ≤2; no individual subscore >1; rectal bleeding subscore 0), modified remission (Modified Mayo Score: Total Mayo without Physician's Global Assessment; stool frequency subscore ≤1; rectal bleeding subscore 0; endoscopic subscore ≤1), or endoscopic improvement (Mayo endoscopic subscore ≤1) were analysed. Results: 319 participants were randomised: baseline mean (standard deviation [SD]) age 40.3 (13.8) years; mean (SD) Total Mayo Score 9.0 (1.5); and median (range) disease duration 4.8 (0.24, 36.5) years. Ritlecitinib and brepocitinib were generally safe and well tolerated. At Week 8, a dose–response relationship was observed across all efficacy endpoints for ritlecitinib and brepocitinib. The proportions of participants achieving remission were significantly higher ( P <0.05) with ritlecitinib 70 and 200 mg and brepocitinib 30 and 60 mg vs placebo (Figure 1). The proportions of participants achieving endoscopic improvement and modified remission were significantly higher in all ritlecitinib and brepocitinib groups vs placebo (Figures 2 and 3). Conclusion: Ritlecitinib 70 and 200 mg QD and brepocitinib 30 and 60 mg QD demonstrated significant improvement in remission, modified remission, and endoscopic improvement in participants with moderate to severe active ulcerative colitis.